An experimental study on shear reinforcement in RC beams using CFRP-bars - Kobraei, M.; Jumaat, Mohd Zamin; Shafigh, P. (Scientific Research and Essays, 2011)
Fibre reinforced polymer (FRP) as an alternative to steel in reinforced concrete (RC) beams has become increasingly popular. The merits of FRP include high strength to weight ratio and corrosion resistance, and its advantages cannot be ignored in civil engineering. Consequently, FRP has attracted considerable interest from researchers. In this research, the effects of using CFRP bars as shear reinforcement instead of stirrups in RC beams have been investigated. All beams were cast using a high strength concrete (HSC), which was also a self-compacting concrete (SCC). For this new idea, modes of failure for seven laboratory specimens, including a comparison of the ultimate moment capacity of beams, load-deflection control, load of first crack, crack width and position of the neutral axis (N.A.) were analysed. The results show that using carbon fibre reinforced polymer (CFRP) shear reinforcement can be an acceptable alternative for normal stirrups in RC beams.